Glutaraldehyde cross-linking of amniotic membranes affects their nanofibrous structures and limbal epithelial cell culture characteristics - Lai JY (Dove Medical Press, 2013)
Jui-Yang Lai,1–3 David Hui-Kang Ma4,5 1Institute of Biochemical and Biomedical Engineering, 2Biomedical Engineering Research Center, 3Molecular Medicine Research Center, Chang Gung University, Taoyuan, Taiwan; 4Limbal Stem Cell Laboratory, Department of Ophthalmology, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 5Department of Chinese Medicine, Chang Gung University, Taoyuan, Taiwan Abstract: Given that the cells can sense nanometer dimensions, the chemical cross-linking-mediated alteration in fibrillar structure of collagenous tissue scaffolds is critical to determining their cell culture performances. This article explores, for the first time, the effect of nanofibrous structure of glutaraldehyde (GTA) cross-linked amniotic membrane (AM) on limbal epithelial cell (LEC) cultivation. Results of ninhydrin assays demonstrated that the amount of new cross-links formed between the collagen chains is significantly increased with increasing the cross-linking time from 1 to 24 hours. By transmission electron microscopy, the AM treated with GTA for a longer duration exhibited a greater extent of molecular aggregation, thereby leading to a considerable increase in nanofiber diameter and resistance against collagenase degradation. In vitro biocompatibility studies showed that the samples cross-linked with GTA for 24 hours are not well-tolerated by the human corneal epithelial cell cultures. When the treatment duration is less than 6 hours, the biological tissues cross-linked with GTA for a longer time may cause slight reductions in 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt, and anti-inflammatory activities. Nevertheless, significant collagen molecular aggregation also enhances the stemness gene expression, indicating a high ability of these AM matrices to preserve the progenitors of LECs in vitro. It is concluded that GTA cross-linking of collagenous tissue materials may affect their nanofibrous structures and corneal epithelial stem cell culture characteristics. The AM treated with GTA for 6 hours holds promise for use as a niche for the expansion and transplantation of limbal epithelial progenitor cells. Keywords: glutaraldehyde, amniotic membrane, nanofibrous structure, limbal epithelial cell, stemness